Situation Report: Romania, 21 September 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Changes in State Organization New Measures on Education Statutes of the Romanian Consulting Institute Incentives for the Enterprises for the Mechanization of Agriculture Students "Volunteer" for Fall Harvesting Church Relations Relations with West Germany Military Contacts with China Continue Prominent Americans Visit Romania Foreign Economic Relations